Clinical Presentation and Outcomes of Acute Disseminated Encephalomyelitis in Adults Worldwide: Systematic Review and Meta-Analysis - Li, Kunyi; Li, Maolin; Wen, Lan; Wang, Qiancheng; Ding, Xin; Wang, Jian (Frontiers in Immunology, 2022)
Background: Acute disseminated encephalomyelitis (ADEM) is a rare demyelinating disorder that is often misdiagnosed. To improve early diagnosis, we performed a systematic review and meta-analysis of clinical features, outcomes for ADEM in adults. Methods: The PubMed, Embase, Web of Science and Cochrane Library databases were searched for studies reporting the clinical features of adults with ADEM between January 1990 and May 2021. A random-effects meta-analysis model was used to pool data on clinical features and functional outcomes. Results: Twelve studies examining 437 adults with ADEM met the inclusion criteria. Overall, the clinical features and diagnostic findings observed in more than two-thirds of the patients were white matter lesions (87.1%, 95% confidence interval [CI]=75-95.6), polyfocal onset (80.5%, 95% CI=50.5-98.9) and pyramidal signs (68.7%, 95% CI =40.0-91.9). The mortality rate was 7.8% (95% CI = 3.3–13.5), and the risk of residual deficits was 47.5% (95% CI = 31.8–63.4). Conclusions: Adults with ADEM had worse outcomes than children. Clinicians should maintain high clinical suspicion for patients presenting with certain clinical features and diagnostic findings.